Tinjauan ‘Urf terhadap Pandangan Tokoh Masyarakat tentang Perkawinan di Bawah Umur Tanpa Dispensasi di Jorong Lubuak Simato - Gina Emora Putri; Fauzan Fauzan (Lembaga Yasin AlSys, 2026)
Although underage marriage without dispensation still occurs in various regions, this practice continues to generate debate between state positive law, Islamic law, and the customs prevailing in society. This study aims to analyze community leaders’ views on the practice of underage marriage without dispensation and to examine it from the perspective of ‘urf in Islamic law in Jorong Lubuak Simato. This study used a qualitative method with a descriptive approach. Data were obtained through interviews with community leaders, customary leaders, religious leaders, and related parties, and were then analyzed using descriptive qualitative analysis techniques. The results showed that some community leaders still justified the practice of underage marriage without dispensation on the grounds of preventing promiscuity, immoral acts, and concealing family disgrace, especially in cases of pregnancy outside marriage. However, community leaders also realized that the practice gives rise to various negative impacts, such as emotional immaturity, economic instability, and health risks for young couples. Viewed from the perspective of ‘urf, this practice can be categorized as ‘urf fasid because it is contrary to the prevailing statutory regulations, particularly Law Number 16 of 2019 concerning the minimum age for marriage. Nevertheless, under certain emergency conditions, the practice is regarded as an effort to avoid greater harm. This study emphasizes the importance of the role of community leaders, families, and the government in providing education and undertaking efforts to prevent underage marriage through social, religious, and legal approaches.